Adoption of improved biomass stoves and stove/fuel stacking in the REACCTING intervention study in Northern Ghana. (July 2019) - Dickinson, Katherine L.; Piedrahita, Ricardo; Coffey, Evan R.; Kanyomse, Ernest; Alirigia, Rex; Molnar, Timothy; Hagar, Yolanda; Hannigan, Michael P.; Oduro, Abraham Rexford; Wiedinmyer, Christine
Abstract: In order to support transitions away from open-fire cooking and toward cleaner household energy systems, a better understanding of users' technology adoption patterns and preferences is needed. This paper highlights key factors influencing use of two types of biomass-burning stoves provided through the REACCTING (Research on Emissions, Air quality, Climate, and Cooking Technology in Northern Ghana) randomized intervention study. We examine traditional and improved stove use over a two year follow up period, finding that the more basic rocket stove was used at a higher rate than the higher-tech gasifier stove. While stove use patterns varied by stove group, region, primary cook occupation, and socioeconomic status, use of traditional stoves remained high across most groups. Users perceived that improved stoves were less suitable for cooking a staple dish, Tuo Zaafi (TZ), and technical problems (e.g., battery failures with the gasifier stove) also limited the effectiveness of the intervention. Moving forward, household energy policies should prioritize a range of technologies that have potential to meet local needs while delivering meaningful health and/or environmental benefits, recognizing that stove and fuel "stacking" is likely to persist. A greater focus on markets and enabling environments is needed to support sustainable and scalable energy transitions. Highlights: In Northern Ghana, cooking with solid fuels produces harmful household air pollution. The REACCTING study provided households with improved biomass cookstoves for free. A basic rocket stove was used more than a higher tech gasifier stove. Stove stacking (continued use of traditional stoves) remained high throughout the study. Stoves' durability and suitability for cooking local dishes limited adoption.